Von unsichtbarer Hand – Germanistik im Wandel der Zeit - Tichy, Ellen (2022)
The article addresses the development of curricula for German study programs in Central Eastern Europe Countries over the past 70 years, from the post-war period to the present. These are shaped by social framework conditions and historical factors, such as the end of the war in 1945, the years directly following, membership of the so-called communist Eastern Bloc, and membership in the EU in 2004 and 2007. The political change of 1989/1990 marked one of the most important milestones; a period began in which western languages and the German language flourished in German departments; only with demographic change has enrollment dropped rapidly since the turn of the millennium. Already in the first decade of the reunification, German institutes “lose” their graduates in fields of jobs that are not oriented towards the humanities, with international companies with business contacts in German-speaking countries taking first place. Today, the majority of universities and German studies institutes are reacting to the pragmatic demands of the labor market and are modifying the range of courses, even if this is at the expense of traditional curricular content.
Keywords: Curricula of German Studies courses; core competencies; German Studies; Central Eastern Europe; labor market; demographic change; historical change